Ultrasound measurements and physical fitness of elite youth basketball players - Lisón, J. F.; García-Herreros, S.; Ricart, B.; Godoy, E. J.; Nozal, S.; Cotolí-Suarez, P.; Jordán-López, J.; Amer-Cuenca, J. J.; Salvador-Coloma, P. (International Journal of Sports Medicine, 2023)
The countermovement jump, the V-cut test, the muscle thickness and the adjacent subcutaneous fat thickness of the gastrocnemius medialis and rectus femoris are important physiological indicators for success in basketball. The aims of this study were to evaluate between-age-category and between-gender differences in these indicators and examine the relationships between physical tests and ultrasound measurements. The measurements were recorded in a sample of 131 elite basketball players (66 males) who played in three age-categories (U14, U16, or U18). We performed two-way analysis of covariance tests and age-adjusted partial correlation analyses. U16 and U18 males showed better performance in the countermovement jump and V-cut tests and lower adjacent subcutaneous fat thickness of the gastrocnemius medialis and rectus femoris compared to the U14 males (p=.001) and to age-category equivalent female players (p=.001). Comparisons between the age categories in females did not show significant differences in any of the study variables. Adjacent subcutaneous fat thickness of the gastrocnemius medialis explained 22.3% of the variation for the countermovement jump result and 12.9% of the variation for the V-cut result in males (p<.01). This study is the first to show the association and predictive role of subcutaneous fat thickness measured by ultrasound in physical performance of male and female elite youth basketball players.